Pengaruh Metode (SQ3R) Berbantuan Pohon Literasi Terhadap Peningkatan Hasil Belajar Siswa Kelas V - Amin, H.; Julkifli, Julkifli (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Survey, Question, Read, Recite, And Review (SQ3R) Method. This method is a reading plan consisting of surveying the content, making questions, reading the content, telling the reading content, and reviewing the reading. Also, the SQ3R method is an integrated study plan to understand and master the reading content. This study aims to determine the effect of using the SQ3R method assisted by literacy trees on improving the learning outcomes of grade V students of SDN Inpres Padende in the 2023/2024 academic year. This type of research is pre-experimental with a quantitative approach. The population is all students from grades I to VI totaling 113 students. The sample used was grade V students totaling 17 students involving one class as the experimental class only. The sampling technique used a purposive sample. Data were obtained through pretest and posttest then analyzed using the t-test. Based on the initial test at the time of the pretest, an average of 65 was obtained, the final test results at the time of the posttest showed an average of 95. The final test data were analyzed using the t-test, the results of the t-test obtained a t-count of 61.36 and a t-table of 86.33. The t-count was obtained to be greater than the t-table at an error level of 5% and a dk of 16. Based on the proposed hypothesis, there is an effect of using the SQ3R method assisted by literacy trees on improving the learning outcomes of class V students of SDN Inpres Padende in 2023/2024.